Self-Efficacy: The Perception of Self-Preparedness for Leaving Institutional Care and Becoming an Independent Individual - Veronika Stenclová (European Scientific Journal, ESJ, 2020)
The family is the main socializing factor for the child and it should perform its role in relation to the healthy development of the child’s personality. If the family fails systematically to perform its functions, another possibility of securing the child's needs would be sought. Children's Home is a type of institutional facility in the Czech Republic where a child from a dysfunctional family can get into. It mainly serves as a pedagogical, educational, and social stimulant for the children. Despite the fact that the children's homes are trying to stimulate the family environment as best as possible, they can never completely replace and restore all family functions. Children living long-term in institutional care often have problems in the psychological and social areas. Their socialization and successful functioning in the society is in many ways difficult and complicated. The paper presents partial results from a quantitative research that focuses on the relationship between self-efficacy of the respondents and their sense of preparation for leaving the children's home as independent persons. Data was collected using a questionnaire consisting of two parts, standardized and non-standardized. The target group used was children’s home clients within the age of 17 to 26, who were soon expected to leave the children's home for the purpose of becoming independent. The essential research sample consisted of 263 clients of public children's homes and the selective sample included 208 respondents. The data was then statistically verified using Shapiro-Wilk normality test and Mann-Whitney test. The correlation between variables was determined by the Spearman correlation coefficient. It was proven that clients who evaluate their self-efficacy better also feel better prepared to leave the children's home than low self-efficacy clients.